2017
DOI: 10.2147/tcrm.s139631
|View full text |Cite
|
Sign up to set email alerts
|

Management of traumatic tympanic membrane perforation: a comparative study

Abstract: This prospective study was conducted to evaluate the efficacy of sea buckthorn oil patches in treating traumatic tympanic membrane (TM) perforations. We enrolled 370 patients with traumatic TM perforations of different sizes. These patients were randomly assigned to control group and treatment group. In the treatment group, a sterile cotton patch with sea buckthorn oil was used to cover the TM perforations. In the control group, patients were treated with a sterile cotton patch. The healing rate and time were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
3
13
0
1
Order By: Relevance
“…7 The mean age and commonest age of presentation of this study is also comparable with results of Al-Juboori from Iraq and Gao and colleagues from china and some other studies. 8,9 In current study amongst the cause of TTMP, slap trauma was most common (70.2%, n-80), subsequently trauma due to blast was found in 17 patients (14.9%), which is keeping with results of Ahluwalia, Al-Juboori, Singh, Irfan, Rai, who also reported that TTMP was mainly due to slap trauma to the ears. 7,8,[10][11][12] However etiologic factors of this study differs from that of, Ravi, Dawood, Sannigrahi, and Al-Obiedi where traumatic tympanic perforation was predominantly caused by blast injuries while in one study road traffic accidents was main cause of tympanic membrane perforation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…7 The mean age and commonest age of presentation of this study is also comparable with results of Al-Juboori from Iraq and Gao and colleagues from china and some other studies. 8,9 In current study amongst the cause of TTMP, slap trauma was most common (70.2%, n-80), subsequently trauma due to blast was found in 17 patients (14.9%), which is keeping with results of Ahluwalia, Al-Juboori, Singh, Irfan, Rai, who also reported that TTMP was mainly due to slap trauma to the ears. 7,8,[10][11][12] However etiologic factors of this study differs from that of, Ravi, Dawood, Sannigrahi, and Al-Obiedi where traumatic tympanic perforation was predominantly caused by blast injuries while in one study road traffic accidents was main cause of tympanic membrane perforation.…”
Section: Discussionsupporting
confidence: 88%
“… 7 The mean age and commonest age of presentation of this study is also comparable with results of Al-Juboori from Iraq and Gao and colleagues from china and some other studies. 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…No higher prevalence of perforations was found in patients under 7 years of age. 19 Results that agree with those published by Brian et al In 2010, where they found an efficiency in the closure of perforations between 70% and 100%, and those of Ryan et al 13 In 2016, with a closure percentage between 35% and 94%, 20 which, although lower than in adults, not negligible in terms of effectiveness. They also do not suggest a strict minimum age to perform this type of surgical procedure, however, some authors propose performing this type of surgical procedure, even in patients aged 4 years.…”
Section: Discussionsupporting
confidence: 84%
“…21,22 In this type of population, the most frequent tympanic perforations are secondary to myringotomy with ventilation tubes, AOM or trauma. 20 Regarding comorbidities, chronic otitis media was related to a higher probability of postoperative reperforation, results similar to those reported by Sajid et al In 2017 12 and by Heo et al 18 In 2017, 23 where it was found that this factor decreases 3.4% the probability of postoperative closure. Likewise, chronic otitis media was also the main cause for which the tympanic membranes were perforated in our study.…”
Section: Discussionsupporting
confidence: 83%
“…Hippophae fructus oil (HFO), a traditional Chinese herb extracted from Hippophae fructus, 8‐10 is composed of vitamin C, amino acids, and essential trace elements (e.g., zinc), which can enhance the proliferation of TM epithelial stem cells, promote their migration to lesions and induce blood vessel dilatation 9,10 . During the past few decades, HFO has been applied for the clinical treatment of TM perforation with satisfactory outcomes 8 . However, the biological mechanism of HFO therapy for TM regeneration remains unclear, and the main compounds of HFO that promote TM healing require further exploration.…”
Section: Introductionmentioning
confidence: 99%